Youth Shifting Identities, Moving Aspirations, Changing Social Norms, and Positive Uncertainty in Ethiopia and Nepal. (December 2022) - Johnson, Vicky; West, Andy
This article explores uncertainty and aspiration in the everyday lives of marginalised youth in fragile and conflict-affected areas of Ethiopia and Nepal. The concept referred to as 'positive uncertainty' was developed through analysis of 300 qualitative case-study interviews with marginalised young people (15–25 years) across rural and urban research sites as part of the Youth Uncertainty Rights (YOUR) World Research (2016–2019). Six exemplary cases illustrate youth creativity in the face of uncertainty. Drawing on Bauman's theories of community, insecurity, and liquid modernity, the research investigated how youth lived with uncertainty in domains of their everyday lives: how youth felt about their relationships with peers and families and how these relationships were influenced by highly gendered social norms and intersecting aspects of marginalisation in communities. Analysis revealed that youth demonstrate creativity as they navigate uncertainty, negotiate intergenerational power dynamics, and shift their aspirations as they strive to meet adult expectations in contexts of growing unemployment, environmental fragility, and political change across both countries. The analysis of marginalised youth responses to uncertainty, relationships, and norms in fragile environments presented goes beyond the application of Bauman's theories to identify 'positive uncertainty' and further extends understandings of the role of uncertainty in navigating intergenerational relationships.